Study on the Regional and Hierarchical Scheduling Structure of the Sluice Pump Group in the Network of Pearl River Delta - HU Xiaozhang; LI Qingmin; LIU Bingjun; WAN Donghui; LIU Zhuangtian (Renmin Zhujiang)
The river and lake system is the carrier of water circulation and water resources inriver Basin. The pattern of river and lake system interconnection will have a major impact onregional water demand, such as flood control and drainage, water resource utilization andecological environment protection. Taking the Xijiang River and Beijiang River Delta as theresearch object, and taking into full account the information of natural geography, hydrology andhydraulic engineering, this paper analyzes the structure of the river network in delta,establishes the natural nodes and artificial control nodes of the river network, and on such abasis, hierarchically divides the river network in delta according to the water system,embankments, area and creeks., and constructs the regional and hierarchical scheduling structurefor the sluice pump group in the river network area based on the distribution of water resources,water environment, node and important water diversion and drainage channels.